Cannabinoid accumulation in hemp depends on ROS generation and interlinked with morpho-physiological acclimation and plasticity under indoor LED environment - Islam, Md Jahirul; Ryu, Byeong Ryeol; Rahman, Md Hafizur; Rana, Md Soyel; Cheong, Eun Ju; Wang, Myeong-Hyeon; Lim, Jung-Dae; Hossain, Mohammad Anwar; Lim, Young-Seok (Frontiers in Plant Science, 2022)
Manipulation of growth and development of cannabis (Cannabis sativa L.) has received considerable interest by the scientific community due to its high value in medicinal and recreational use worldwide. This study was conducted to investigate the effects of LED spectral changes on reactive oxygen species (ROS) and cannabinoid accumulation by provoking growth, pigmentation, photosynthesis, and secondary metabolites production of cannabis grown in an indoor environment. After three weeks of vegetative growth under greenhouse condition, plants were further grown for 90 days in a plant factory treated with 4 LED light compositions with a canopy-level photosynthetic photon flux density (PPFD) of 300 µmol m−2 s−1 for 16 h. Photosynthetic pigments and photosynthetic rate were linearly increased up to 60 days and then sharply decreased which was found most prominent in L3: MB 240 (Red 85% + Blue 15%) and L4: PF 240 (Red 70% + Blue 30%) LED light compositions. A high concentration of H2O2 was also observed in L3 and L4 treatments which provoked lipid peroxidation in later growth stage. In addition, higher accumulation of cannabinoid was observed under L4 treatment in most cases. It is also evident that higher ROS created a cellular stress in plant as indicated by higher osmolyte synthesis and enzyme activity which initiate quick maturation along with higher cannabinoids accumulation in cannabis plant. Therefore, it can be concluded that ROS metabolism has a crucial role in morpho-physiological acclimation and cannabinoid accumulation in hemp plants. The findings of this study provide further insight on the use of LED light to maximize the production of cannabinoid.